2012
DOI: 10.1111/j.2047-2927.2012.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the haematopoietic effect of testosterone mediated by erythropoietin? The results of a clinical trial in older men

Abstract: SUMMARYThe stimulatory effects of testosterone on erythropoiesis are very well known, but the mechanisms underlying the erythropoietic action of testosterone are still poorly understood, although erythropoietin has long been considered a potential mediator. A total of 108 healthy men >65 years old with serum testosterone concentration <475 ng/dL were recruited by direct mailings to alumni of the University of Pennsylvania and Temple University, and randomized to receive a 60-cm 2 testosterone or placebo patch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 27 publications
(30 reference statements)
3
51
1
1
Order By: Relevance
“…It has been also reported that they respond by clonogenic growth in vitro to certain sex hormones (SexHs), such as prolactin (PRL), androgens, and estrogens [1][2][3]. In further support of this notion, androgens (eg, danazol) are currently employed to treat aplastic anemia patients [4].…”
Section: Introductionmentioning
confidence: 80%
“…It has been also reported that they respond by clonogenic growth in vitro to certain sex hormones (SexHs), such as prolactin (PRL), androgens, and estrogens [1][2][3]. In further support of this notion, androgens (eg, danazol) are currently employed to treat aplastic anemia patients [4].…”
Section: Introductionmentioning
confidence: 80%
“…There were no 'serious' patient-centered adverse events (e.g. cerebrovascular accident, vascular occlusive events, venous thromboembolisms) reported during the study period of 36 months [Maggio et al 2013]. …”
Section: Erythrocytosismentioning
confidence: 99%
“…Snyder et al (1999) noticed that erythrocytosis occurred in 5.5 % of scrotal transdermal users, and the majority of changes took place over the fi rst three months of treatment (24). The frequency of polycythemia (hematocrit over 51 %) was related mainly to supra-physiological serum TST levels.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, within the period of 36 months, Maggio et al (2013) reported, that there were no 'serious' patient-centered adverse events (e.g. cerebrovascular accident, vascular occlusive events, venous thromboembolisms).…”
Section: Discussionmentioning
confidence: 99%